Variable operating conditions in distributed systems: modeling and evaluation. (13th October 2014) - Longo, Francesco; Bruneo, Dario; Distefano, Salvatore; Scarpa, Marco; Xiang, Yang; Pathan, Mukaddim; Wei, Guiyi; Fortino, Giancarlo
Summary Performance and dependability evaluation plays a key role in the design of a broad range of systems, especially when strict requirements need to be met. This is particularly challenging in distributed contexts, where several components may interact among themselves by influencing each other. In this paper, we present an analytical method that allows the study of a class of systems where different operating conditions alternate by changing the stochastic behavior of the system components but still preserving the continuity of the performance and dependability quantities to investigate. The proposed solution technique, based on phase type distributions, Kronecker algebra, and ad‐hoc fitting algorithms, can be applied for the analytical evaluation of a wide class of distributed systems. Examples are provided to show the usefulness and the applicability of the methodology, characterizing and investigating different performance and dependability aspects of three distributed computing systems, that is, a connection‐oriented network, an Internet of Things application, and an Infrastructure‐as‐a‐Service Cloud. Copyright © 2014 John Wiley & Sons, Ltd.